Optimalisasi Skrining Biomarker Metabolik Untuk Deteksi Dini PTM Pada Lansia - Fitri Handayani Siregar; Sri Muri Dasa wardhani; Ikhsan Ibrahim Pohan; Rismaidah Purba; Helmiwati Helmiwati; Rizki Kurniaty Hasibuan; Latifah Ningrum Abdillah; Sri Handayani Siregar; Leo Pardon Sipayung (Universitas Negeri Gorontalo, 2026)
Non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, and dyslipidemia remain the leading causes of morbidity and mortality among the elderly. Early detection through metabolic biomarker screening is essential to reduce complications and improve quality of life. This community service program aimed to optimize metabolic biomarker screening among elderly residents in Rugemuk Village, Pantai Labu District, Deli Serdang. The descriptive method was applied through blood pressure measurement, fasting blood glucose, total cholesterol testing using Point of Care Testing (POCT), and vitamin B12 supplementation. A total of 85 elderly participants were involved over three days. Results showed that 38% of participants had hypertension, 29% had borderline cholesterol, and 22% had elevated glucose levels. Health education increased knowledge scores by 30% post-intervention. These findings highlight the effectiveness of integrated community-based screening in detecting metabolic risks and improving awareness of NCD prevention. Sustainable collaboration with local health cadres and primary health centers is recommended to strengthen routine screening programs.